Effect of diet-induced obesity and metabolic syndrome on skeletal muscles of Ossabaw miniature swine - Clark, Bradley A. (American Physiological Society, 2011)
Ossabaw swine fed excess kilocalorie diet develop metabolic syndrome (MS) characterized by obesity, hypertension, insulin resistance, and glucose intolerance with/without dyslipidemia. The purpose of this study was to test the hypothesis that MS would have a detrimental effect on skeletal muscle structure and cause changes in the expression of myosin heavy chains (MHCs). Adult male Ossabaw swine were fed for 24 wk high-fructose or high-fat/cholesterol/fructose diets to induce normolipidemic MS (MetS) or dyslipidemic MS (DMetS), respectively, and were compared with the lean swine on control diet. MetS swine showed mild MS, lacking increases in total and low density lipoprotein (LDL) cholesterol, both of which were highly upregulated in DMetS swine. There was an ∼1.2-fold increase in the cross-sectional areas of muscle fibers in MetS and DMetS groups compared with control for biceps femoris and plantaris muscles. In plantaris muscles, DMetS diet caused an ∼2-fold decrease in slow MHC mRNA and protein expression and an ∼1.2- to 1.8-fold increase in the number of intramyocellular lipid (IMCL) droplets without large changes in the size of the droplets. There was a trend to the decrease in slow MHC expression in muscles of swine on MetS diet. The number of IMCL droplets in muscle fibers of the MetS group was comparable to controls. These data correlate well with the data on total plasma cholesterol (control = 60, MetS = 70, and DMetS = 298 mg/dl) and LDL (control = 29, MetS = 30, and DMetS = 232 mg/dl). We conclude that structural changes observed in skeletal muscle of obese Ossabaw swine correlate with those previously reported for obese humans.